MENGGAGAS MODEL PEMBELAJARAN IPS TERPADU BERBASIS TEOLOGI SOSIAL - Ni Made Suryadini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
One of the compulsory lessons taught at the junior secondary level in social science (IPS). Social Sciences is different from monodisciplinary disciplines. Social studies is integrated among social science disciplines. Social Sciences (IPS) has the equivalent term with social studies in the United States. The Social Theology based learning model seeks to raise students' religious awareness to respect their environment. Knowledge, religious awareness and activities of students about the environment and preservation of meaningful environmental functions as a product of environmental care habitus. Social Theology-based social studies as a syntax in learning models include: (a) orientation, (b) elicitation of ideas, (c) idea restructuring, (d) application, and (e) review. The environment can not be separated in human life, therefore between humans and the environment there is a reciprocal relationship where the environment affects humans and vice versa humans also affect the environment. Likewise in the teaching and learning process, the environment is an influential learning resource in the learning process and the development of students. With the strengthening of religious propositions, it is expected that students' awareness to participate in preserving the environment will be stronger. The direct experience can better understand the understanding or basic ideas in social studies lessons. In addition, the method used must be more interesting so that students will be focused on the concepts conveyed.Keyword: Social studies, learning, teologi sosial